2024
DOI: 10.3389/fimmu.2024.1348156
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic targets to enhance antitumor immune response through the induction of tertiary lymphoid structures

Quadri Ajibola Omotesho,
Alejandro Escamilla,
Elisabeth Pérez-Ruiz
et al.

Abstract: Tertiary lymphoid structures (TLS) are ectopic lymphoid aggregates found in sites of chronic inflammation such as tumors and autoimmune diseases. The discovery that TLS formation at tumor sites correlated with good patient prognosis has triggered extensive research into various techniques to induce their formation at the tumor microenvironment (TME). One strategy is the exogenous induction of specific cytokines and chemokine expression in murine models. However, applying such systemic chemokine expression can … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 212 publications
0
0
0
Order By: Relevance
“…In a recent study, an identified CD88 - CD1c + CD163 + progenitor DC subset was found to display a distinctive ability to prime CD8 T cells that express a tissue-homing signature with the epithelial homing alpha-E integrin (CD103) ( 58 ). Studies in mouse models have demonstrated that delivery of TBX21 (encoding transcription factor T-bet) gene-modified DCs promotes Th1 and Tc1 cell infiltration and the formation of TLSs in sarcoma tumors ( 59 ). Additionally, intratumoral infusion of CCL21 over-expressed DCs was shown to increase intratumoral CD8 T cell infiltration and reduce tumor burdens in a transgenic lung cancer mouse model ( 60 ).…”
Section: Adhesion Signalings In Regulating the Transmigration Program...mentioning
confidence: 99%
“…In a recent study, an identified CD88 - CD1c + CD163 + progenitor DC subset was found to display a distinctive ability to prime CD8 T cells that express a tissue-homing signature with the epithelial homing alpha-E integrin (CD103) ( 58 ). Studies in mouse models have demonstrated that delivery of TBX21 (encoding transcription factor T-bet) gene-modified DCs promotes Th1 and Tc1 cell infiltration and the formation of TLSs in sarcoma tumors ( 59 ). Additionally, intratumoral infusion of CCL21 over-expressed DCs was shown to increase intratumoral CD8 T cell infiltration and reduce tumor burdens in a transgenic lung cancer mouse model ( 60 ).…”
Section: Adhesion Signalings In Regulating the Transmigration Program...mentioning
confidence: 99%